2014
DOI: 10.3126/on.v11i2.9647
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Feeding Habits of Cyprinus carpio in Relation with Water Quality of Integrated Rice-Fish Farming Ecosystem

Abstract: This study describes the diets and feeding habits of Cyprinus carpio in integrated rice-fish farming system in the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh, Central Bangladesh during May 1999 to August 1999. Percentage of frequency of occurrence and percentage in number methods were applied for the qualitative and quantitative estimation of plankton. The water quality parameters recorded during the study were within the suitable range for optimal fish growth and plankton popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Based on  15 N values, Baetidae showed the highest trophic position, followed by the fish species and C. nilotica. All studied fish species are omnivorous, which explains these results (Bloomer et al, 2007;Jimoh et al, 2011;Mondol et al, 2013). The high trophic position of Baetidae was not expected, as Palmer et al (1993) showed that the gut content of mayfly larvae consisted mainly of amorphous detritus.…”
Section: Trophic Transfer Through the Food Webmentioning
confidence: 88%
“…Based on  15 N values, Baetidae showed the highest trophic position, followed by the fish species and C. nilotica. All studied fish species are omnivorous, which explains these results (Bloomer et al, 2007;Jimoh et al, 2011;Mondol et al, 2013). The high trophic position of Baetidae was not expected, as Palmer et al (1993) showed that the gut content of mayfly larvae consisted mainly of amorphous detritus.…”
Section: Trophic Transfer Through the Food Webmentioning
confidence: 88%
“…Moreover, data on the feeding habits of marine fishes, such as the predatory-prey relationship are very helpful in the ecosystem [9]. Information on stomach composition could be useful to fish farmers for multispecies fishery [10,11] and these are important requirements for the Ecopath model [12] used for elucidating aquatic ecosystem functioning and providing critical biological information for fisheries management [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon contributes positively to augmenting the availability of soil nutrients (Wan et al, 2010). Further, the behaviors of fish can induce soil aeration in rice fields (Mondol et al, 2013), while they also control pests and parasites in the rice fields. Certain fish species feed on insects, snails, and other pests that destroy rice plants, reducing the need for chemical pesticides (Frei and Becker, 2005).…”
Section: The Ecological Functions Of Fish In Rice-fish Integrationmentioning
confidence: 99%